2020
DOI: 10.1002/lno.11562
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic energy conversion efficiency in the West Antarctic Peninsula

Abstract: The West Antarctic Peninsula (WAP) is a highly productive polar ecosystem where phytoplankton dynamics are regulated by intense bottom-up control from light and iron availability. Rapid climate change along the WAP is driving shifts in the mixed layer depth and iron availability. Elucidating the relative role of each of these controls and their interactions is crucial for understanding of how primary productivity will change in coming decades. Using a combination of ultra-high-resolution variable chlorophyll f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 73 publications
2
18
0
Order By: Relevance
“…Chla biomass in the surface showed a markedly spatial variation, as well as pico-cells abundance (Figure 2). Generally, the growth and primary productivity of phytoplankton are regulated by macro-(e.g., nitrogen and phosphate) and/or micronutrients (e.g., dissolved iron) (Li et al, 2012a;Chinni et al, 2019;Sherman et al, 2020). In the surveyed areas, the surface N and the P levels were <1.0 and 0.10 µM (data not shown), with the N:P ratio being lower than 16, indicating a nitrogen limitation (Li et al, 2012a), especially in the southern Indian Ocean (Wilcoxon test, p < 0.05), where Chla biomass and picocells abundance were lower.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Chla biomass in the surface showed a markedly spatial variation, as well as pico-cells abundance (Figure 2). Generally, the growth and primary productivity of phytoplankton are regulated by macro-(e.g., nitrogen and phosphate) and/or micronutrients (e.g., dissolved iron) (Li et al, 2012a;Chinni et al, 2019;Sherman et al, 2020). In the surveyed areas, the surface N and the P levels were <1.0 and 0.10 µM (data not shown), with the N:P ratio being lower than 16, indicating a nitrogen limitation (Li et al, 2012a), especially in the southern Indian Ocean (Wilcoxon test, p < 0.05), where Chla biomass and picocells abundance were lower.…”
Section: Discussionmentioning
confidence: 91%
“…Major pigments of Synechococcus to constitute the lightharvesting complexes are phycobilisomes (Sliwińska-Wilczewska et al, 2020), while that of Prochlorococcus are divinyl derivatives Chla/b (Ralf and Repeta, 1992); such a pigment difference may vary their light-harvesting abilities, thus leading to the differential photosynthetic responses to the acutely increased temperature between the surface and DCM layers. Larger σ PSII prevailed in the southern part of the surveyed areas where phytoplankton may have adaptively improved its light-harvesting abilities to sustain growth (Zhu et al, 2017;Sherman et al, 2020), because of the low nutrient status therein (data not shown). The larger σ PSII has also been suggested to be attributed to light-adapted genotypic feature due to niche partition (Jin et al, 2016), evidenced by the higher σ PSII values of phytoplankton assemblages from deep waters.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Given these sources of variability, NPQ relaxation times needed for robust F v / F m measurements are expected to differ significantly across ocean regimes. In cold waters, such as those encountered along our ship track, NPQ relaxation is slower [61], and this may have contributed to the longer-lived quenching observed in our low-light samples. As the spatial and temporal resolution of F v / F m and ETR a measurements are constrained by such acclimation periods, it is recommended that future field deployments of FRRf conduct experiments using natural assemblages to determine the regional minimum relaxation period necessary to achieve steady-state dark-acclimation.…”
Section: Discussionmentioning
confidence: 99%
“…Shallow sediments in the coastal zone can be influential in this supply, as can glaciers that scour underlying rock and sediments prior to supplying freshwater to the coastal seas (Annett et al, 2017;Boyd & Ellwood, 2010;Raiswell, 2011;Sherrell et al, 2018). Stronger glacial discharge to the ocean has the potential to deliver increased micronutrients (Hawkings et al, 2014), and could impact phytoplankton assemblage composition and biomass (Moline et al, 2004;Sherman et al, 2020). For example, Dierssen et al (2002) noted that >70% of the phytoplankton blooms observed offshore of Anvers Island (Figure 1) occurred soon after meltwater pulses from local glaciers.…”
mentioning
confidence: 99%